Challenges of a weight control treatment in Campeche, Mexico. Some considerations from psychoanalysis - Morales, María de los Milagros (2024)
This contribution aims at showing the challenges faced by patients whose treatment for chronic and degenerative diseases implies weight control. Under a qualitative research approach, guided by psychoanalysis, in-depth interviews were conducted and data analyzed through content analysis. Results seem to indicate that the patients’ challenges have three dimensions: a) a socio-structurally institutional one, b) the therapeutic bond, and c) a psychic-drive correlate. It was concluded that patients attribute their main difficulties to the lack of institutional services and to the therapeutic bond; they do not acknowledge the inconsistencies in weight control within their psychic correlate, nor take responsibility for their treatment or self-care. Moreover, institutional shortcomings limit the treatment reach and contribute to the problem chronification.